Eye movements in oral reading by primary school students: The relevance of punctuation marks - Nair Daiane de Souza Sauaia Vansiler; Angela Ines Klein; Romeu Miqueias Szmoski (Káñina)
This study aims to explore the relevance of punctuation marks during oral reading. To achieve this objective, we compared eye movement metrics of two groups of 5th-year students, classified based on the Reading Fluency variable. The fluent reading group (FL) consisted of 27 participants, while 31 participants were in the poor reading fluent group (PF). All participants read three types of text: a simple text with punctuation, a complex text with punctuation and a simple text without punctuation. By analyzing the fixations and saccades, the data suggest that the complexity of the text influences the eye-tracking metrics of the PF group, but not the FL group. On the other hand, the presence of punctuation influence the reading behavior of the FL group, but not the PF group. These findings highlight the influence of punctuation and textual complexity on the dynamics of oral reading and offer valuable insights into how reading fluency is related to text comprehention.